Materiality in information environments: Objects, spaces, and bodies in three outpatient hemodialysis facilities. (18th July 2019) - Veinot, Tiffany C.; Pierce, Casey S.
Abstract : The materiality of information environments, and its role in information behavior, has received little attention. We present an ethnographic study involving 156 hours of observation and 28 patient interviews in outpatient hemodialysis facilities. Using an extended "Semiotic Framework for Information Systems Research, " the findings show that objects, spaces, and bodies were integral to 6 sociomaterial layers of facility information environments: the physical, empiric, syntactic, semantic, pragmatic, and social world. Objects of importance in the information environments included dialysis machines, instruments, records, paper documents, televisions, furniture, thermostats, lighting, and personal possessions. Spatial features, including compartmentalization, displays, distance, proximity, and spatially‐grounded routines, also constituted information environments. The information environments were also shaped by patient immobility, bodily discomforts, and orientation to bodily states. Each sociomaterial layer introduced enablers and constraints to information access, flow, and acceptance; these combined to construct patients primarily as passive recipients of information rather than active seekers and producers of information. A sociomaterial perspective and related focus on objects, spaces, and bodies offers a lens for professional information practice. We contribute information environment design guidance to facilitate such practice and stress that the value of certain sources and types of information can be materially encoded in an environment.